2014
DOI: 10.1103/physrevd.90.064011
|View full text |Cite
|
Sign up to set email alerts
|

Scalar field excited around a rapidly rotating black hole in Chern-Simons modified gravity

Abstract: We discuss a Chern-Simons (CS) scalar field around a rapidly rotating black hole in dynamical CS modified gravity. The CS correction can be obtained perturbatively by considering the Kerr spacetime to be the background. We obtain the CS scalar field solution around the black hole analytically and numerically, assuming a stationary and axisymmetric configuration. The scalar field diverges on the inner horizon when we impose the boundary condition that the scalar field is regular on the outer horizon and vanishe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 41 publications
0
31
0
Order By: Relevance
“…[37] and [39] that upon linearization around a Schwarzschild or slowly rotating BH background, respectively, the dCS field equations admit superluminal mode solutions, which are damped away. Studies of dCS gravity in the background of a Kerr BH revealed that the scalar field diverges on the inner horizon [18]. As described in Sec.…”
Section: W Ell-posedness Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…[37] and [39] that upon linearization around a Schwarzschild or slowly rotating BH background, respectively, the dCS field equations admit superluminal mode solutions, which are damped away. Studies of dCS gravity in the background of a Kerr BH revealed that the scalar field diverges on the inner horizon [18]. As described in Sec.…”
Section: W Ell-posedness Discussionmentioning
confidence: 92%
“…No complete solution for a rotating BH in dCS theory is known, but see Refs. [12][13][14][15][16][17][18][19] for perturbative calculations. Exploring dynamical BH solu tions provides the possibility to explore gravity in the strong-field regime.…”
Section: R2+ F 2{e)rabrab + H {0)rabcdrabcd + F A(e)* *Rrmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the post-GR corrections for the dynamic model has been considered through the study of rapidly rotating black holes in the decoupling limit [34,35]. Such work is important because of the possibility to constraint the theory in the strong field regime.…”
Section: Brief Review Of Other Forms Of the Kinetic Termmentioning
confidence: 99%